SGLT2 inhibitor ipragliflozin attenuates breast cancer cell proliferation - Komatsu, Shiho; Nomiyama, Takashi; Numata, Tomohiro; Kawanami, Takako; Hamaguchi, Yuriko; Iwaya, Chikayo; Horikawa, Tsuyoshi; Fujimura-Tanaka, Yuki; Hamanoue, Nobuya; Motonaga, Ryoko; Tanabe, Makito; Inoue, Ryuji; et al. (ENDOCRINE JOURNAL, 2020)
Cancer is currently one of the major causes of death in patients with type 2 diabetes mellitus. We previously reported the beneficial effects of the glucagon-like peptide-1 receptor agonist exendin-4 against prostate and breast cancer. In the present study, we examined the anti-cancer effect of the sodium-glucose cotransporter 2 (SGLT2) inhibitor ipragliflozin using a breast cancer model. In human breast cancer MCF-7 cells, SGLT2 expression was detected using both RT-PCR and immunohistochemistry. Ipragliflozin at 1–50 μM significantly and dose-dependently suppressed the growth of MCF-7 cells. BrdU assay also revealed that ipragliflozin attenuated the proliferation of MCF-7 cells in a dose-dependent manner. Because the effect of ipragliflozin against breast cancer cells was completely canceled by knocking down SGLT2, ipragliflozin could act via inhibiting SGLT2. We next measured membrane potential and whole-cell current using the patch clamp technique. When we treated MCF-7 cells with ipragliflozin or glucose-free medium, membrane hyperpolarization was observed. In addition, glucose-free medium and knockdown of SGLT2 by siRNA suppressed the glucose-induced whole-cell current of MCF-7 cells, suggesting that ipragliflozin inhibits sodium and glucose cotransport through SGLT2. Furthermore, JC-1 green fluorescence was significantly increased by ipragliflozin, suggesting the change of mitochondrial membrane potential. These findings suggest that the SGLT2 inhibitor ipragliflozin attenuates breast cancer cell proliferation via membrane hyperpolarization and mitochondrial membrane instability.